The Effectiveness of Self-Compassion Training on Self-Criticism and Academic Achievement in Female Students with Generalized Anxiety Disorder - Veiskarami, Hasan Ali; Rezaei, Fatemeh; Mansouri, Leila (International Journal of Applied Behavioral Sciences, 2017)
Introduction: generalized anxiety disorder (GAD) is the most common type of anxiety disorder and has high rates of comorbidity with other psychiatric disorders. Sever anxiety is the main diagnostic criteria for GAD.The purpose of this study was to investigate the effectiveness of cognitive self-compassion training on self criticism and academic achievement in second grade female high school students with GAD.Methods: The present experimental study included pre-test, post-test with the control group design. The statistical population of this study consisted of all female second grade students of high schools in Izeh city in the academic year of 2015-2016. Screening was conducted and 302 participants completed the Penn State Worry Questionnaires, Then 40 individuals suffering GAD identified and were assigned randomly to experimental and control groups. The instruments used in this study was Slef-Criticism Questionnaire and student's average scores were used to measure academic achievement. The experimental group received self-compassion training for ten 90-minutes sessions, one session in a week lasting for two months. Analysis of the data was done using descriptive and inferential tests such as covariance analysis was conducted.Results: Experimental group showed significant decrease in self-criticism after being Trained (P<0/001). It also increased academic achievement in experimental group (P<0/001).Conclusion: Based on the result we can say that cognitive self-compassion training is an important factor in reducing self-criticism and to improve academic achievement in students suffer from GAD.